(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
Zn doped Cu ferrite of the composition Cu1-xZnxFe2O4 ferrites for x = 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 prepared by standard double sintering ceramic technique. SEM micrograph of all the samples revealed that the grain sizes decrease gradually with the increase of Zn content and has great influence on the magnetic and transport properties. Permeability is found to increase with increase in Zn content up to x = 0.4 and then slightly decreases with further increase in Zn. The values of relative quality factor (RFQ) changes with Zn concentration. Room temperature DC resistivity changes significantly with Zn addition. The variation of the resistivity versus frequency was studied and the dielectric constant of the system has a variation quite opposite to that of the AC resistivity. Dielectric constant shows the normal behaviour of the ferrite materials that can be explained by the interfacial polarization as predicted by Maxwell and Wagner. Key words: Microstructure; Initial permeability; Dielectric constant; DC resistivity DOI: 10.3329/jbas.v34i1.5486 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 1-8, 2010